TAX AVOIDANCE IN THE MANUFACTURING INDUSTRY: THE EFFECTS OF CSR DISCLOSURE AND EARNINGS MANAGEMENT - Lukmana, Istiqomah Nova; Puspita, Rosana Eri (Ultimaccounting Jurnal Ilmu Akuntansi, 2023)
Abstract” Tax avoidance in Indonesia must be considered due to the trend of tax avoidance carried out by taxpayers, which causes the state to experience losses. Based on data from the Directorate General of Taxes of the Ministry of Finance, due to tax avoidance, it can cost Indonesia up to 4.86 billion U.S. dollars, equivalent to Rp 68.7 trillion if exchanged into Rupiah per year. This study aims to determine the effect of disclosure of Corporate Social Responsibility (CSR) and earnings management on tax avoidance, with financial performance as an intervening variable. This research includes quantitative research with secondary data. The population in this study are companies registered at Jakarta Islamic Index 70, and the samples used are manufacturing companies registered at Jakarta Islamic Index 2018–2022. The method used is Path Analysis by using the software eviews10. The results of this study show that Corporate Social Responsibility and earnings management have no significant positive effect on tax avoidance. Financial performance has a significant negative effect on tax avoidance. CSR has a significant positive effect on financial performance, and earnings management has a significant negative effect on financial performance. Meanwhile, financial performance cannot mediate CSR and earnings management for tax avoidance. Keywords: : CSR; Earnings Management; Tax Avoidance; Financial Performance